(untitled) (PANGEEA, 2025)
The cadastre maintenance is a technical, economic and legal operation that ensures updating the cadastral documents. Using cadastral data with maximum efficiency by individual beneficiaries can not be ensured unless these data reflect reality on the landscape at any time, regarding real estates (shape, size, quality, ownership, destination, use, etc.). This can be ensured only through a systematic activity of updating the cadastre.